Functional MRI in conscious rats using a chronically implanted surface coil. Issue 3 (15th May 2013) - Martin, Chris J.; Kennerley, Aneurin J.; Berwick, Jason; Port, Michael; Mayhew, John E.W.
<x xml:space="preserve">Abstract</x> Purpose To establish procedures for functional MRI (fMRI) in rats without the need for anesthetic agents. Materials and Methods Rats were trained to habituate to restraint in a harness and scanner noise. Under anesthesia, rats were then prepared with a cranial implant that permitted stabilization of the head during subsequent imaging experiments. The cranial implant included an radiofrequency (RF) coil that was used to transmit and receive radiofrequency signals during imaging. Further training was then conducted to habituate the animals to head fixation whilst in the MR scanner. Results Using this method, we were able to successfully and repeatedly record BOLD fMRI responses to hypercapnia and whisker stimulation in awake rats. Electrical stimulation of the whisker pad produced a ∼7% increase in BOLD signal in the corresponding barrel cortex as well as adjacent negative BOLD responses, whilst hypercapnia produced larger increases in BOLD signal amplitude. Conclusion This methodology leaves the face and limbs free from obstruction, making possible a range of behavioral or sensory stimulation protocols. Further development of this animal model could enable traditional behavioral neuroscience techniques to be combined with modern functional neuroimaging. J. Magn. Reson. Imaging 2013;38:739–744. © 2013 Wiley Periodicals, Inc.